2009
DOI: 10.1177/1087054709347261
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Well-being in College Students With and Without a Diagnosis of ADHD

Abstract: College students with a diagnosis of ADHD may represent an especially resilient group. Future studies should investigate competencies of students with ADHD who have achieved success against the odds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
1
47
2
9
Order By: Relevance
“…While adversity is often negatively related to well-being (Breslau et al 1999;Turner and Lloyd 1995), recent evidence suggests that adversity may also foster resilience, i.e., individuals who experience moderate adversity may be better able to cope with stressful situations or failure and, therefore, report higher well-being (Seery et al 2010;Seery, et al 2013). By experiencing the negative consequences of ADHD from early childhood, those individuals may develop a higher resistance to failure as well as ways to cope with adversity and achieve success against significant odds (Wilmshurst et al 2011). In particular, high-functioning adults who show ADHD-like behavior may exhibit greater resilience to disappointments.…”
Section: Adhd-like Behavior and The Work Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While adversity is often negatively related to well-being (Breslau et al 1999;Turner and Lloyd 1995), recent evidence suggests that adversity may also foster resilience, i.e., individuals who experience moderate adversity may be better able to cope with stressful situations or failure and, therefore, report higher well-being (Seery et al 2010;Seery, et al 2013). By experiencing the negative consequences of ADHD from early childhood, those individuals may develop a higher resistance to failure as well as ways to cope with adversity and achieve success against significant odds (Wilmshurst et al 2011). In particular, high-functioning adults who show ADHD-like behavior may exhibit greater resilience to disappointments.…”
Section: Adhd-like Behavior and The Work Environmentmentioning
confidence: 99%
“…For example, taste for variety may drive individuals who exhibit ADHD-like behavior to pursue an entrepreneurial career because they often search for varied sensory input to satisfy their chronic underarousal, and taste for variety is also related to entrepreneurship (Å stebro and Thompson 2011). Another potential mediator is adversity resilience because individuals with ADHD-like behavior are likely to develop ways to cope with adversity and are therefore relatively resilient (Wilmshurst et al 2011), while at the same time, adversity resilience has been related to entrepreneurship (Holland and Shepherd 2013;Markman and Baron 2003;Markman et al 2005;Patel and Thatcher 2014;van Gelderen 2012).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…12 Resilience positively correlates with lower psychological distress and higher well-being. 13,14 Prospective studies suggest that resilience training may improve measures of psychological distress, self-efficacy, and self-esteem in workplace settings, 15,16 with college students, 17 and in patients with diabetes. 18 Most of the resilience training programs, however, entail several weeks of training with a considerable time commitment.…”
Section: Introductionmentioning
confidence: 99%
“…9 Few studies have described characteristics of ADHD individuals that may contribute to the development of resilience. Wilmshurst et al 10 examined psychological well being, self-concept, and academic performance in ADHD-diagnosed college students and found significant differences compared to a control group. In their study, subjects with ADHD reported significantly more support from parents than control students, who reported significantly more support from friends.…”
Section: Introductionmentioning
confidence: 99%